Evaluating an Order Set for Improvement of Quality Outcomes in Diabetic Ketoacidosis. (January 2018) - Joyner Blair, Anna Marie; Hamilton, Bernita K.; Spurlock, Amy
Abstract : The timely management of diabetic ketoacidosis (DKA) is essential to avoid lengthy hospitalizations and poor clinical outcomes. There is often an absence of ownership for glycemic management in hospitalized patients, most notably in those with a diagnosis other than diabetes. Evidence supports the use of evidence-based DKA protocols. The purpose of this project was to determine whether utilization of an evidence-based order set versus an individualized provider approach for the treatment and management of DKA decreases resolution time and occurrences of hypoglycemia and improves clinical outcomes. Preintervention and postintervention retrospective reviews of the electronic medical record of 150 nonpregnant adult patients diagnosed with DKA allowed retrieval of relevant outcome data. Multiple events provided an intensive orientation and development of health care professionals for a systems approach to utilization of the evidence-based order set. Implementation of the institutionally approved evidence-based order set affirmed anticipated outcomes. Results showed improvements in the (a) total length of stay, (b) arrival to intravenous fluid time, (c) intravenous insulin initiation to discontinuation (resolution) time, (d) arrival to subcutaneous insulin administration time, (e) time from initial to sequential laboratory testing, (f) use of a basal, prandial, and correction insulin approach (physiological mimic), and (g) the incidence of hypoglycemia. Outcomes substantiate the importance and need for maintaining an evidence-based and systems approach for the management of DKA.